Determinants of corporate dividend policy in Polish companies listed on WSE - Magdalena Gostkowska-Drzewicka; Ewa Majerowska (e-Finanse: Financial Internet Quarterly, 2019)
The purpose of this paper is to identify the factors influencing the level of dividend payments in the companies listed on the Warsaw Stock Exchange in 1998-2017 as well as to provide empirical evidence for their significance, using a panel data approach. The object of research comprised the companies listed on WSE, as of February 01, 2019. The subject of the analysis are the dividends paid by the companies and the factors potentially influencing the decisions regarding profit distribution. The models estimated for the panel data, based on the theory, allowed selection of the best model, which is the random-effects model. Moreover, these models allowed identification of the factors determining the changes in the level of dividend per share. The best model was the random-effects model. This model allowed identification of the factors impacting the changes in the level of dividend per share, that is, the value of the company's total assets and the history of the company's operation on the stock exchange market. All structural parameters (except the intercept) were positive. It means that growth of each of these variables causes an increase in the dividend per share.
Keywords: G35; C50; L74; 330; dividend policy; economic factors; corporate payout; panel data modelling